Aggregate Economic Shocks, Child Schooling, and Child Health - Ferreira, Francisco H.G.; Schady, Norbert (World Bank, 2012)
Do aggregate income shocks, such as those caused by macroeconomic crises or droughts, reduce child human capital? The answer to this question has important implications for public policy. If shocks reduce investments in children, they may have a long-lasting impact on poverty and its intergenerational transmission. The authors develop a simple framework to analyze the effects of aggregate economic shocks on child schooling and health. They show that the expected effects are theoretically ambiguous because of a tension between income and substitution effects. They then review the recent empirical literature on the subject. In richer countries, like the United States, child health and education outcomes are counter-cyclical: they improve during recessions. In poorer countries, mostly in Africa and low-income Asia, the outcomes are procyclical: infant mortality rises and school enrollment and nutrition fall during recessions. In the middle-income countries of Latin America, the picture is more nuanced: health outcomes are generally procyclical and education outcomes counter-cyclical. Each of these findings is consistent with the simple conceptual framework. The authors discuss possible implications for expenditure allocation.